Effects of Aerobic Exercise on Leukocyte-Mediated Liver Destruction in a Rat Model of Metabolic Syndrome - Fatmanur Er; Leyla Çimen; Ceren Suveren; Canan Yılmaz; Nurten Türközkan (Gazi Medical Journal)
Objective: In this study, the levels of malondialdehyde (MDA), myeloperoxidase (MPO), and 3-nitrotyrosine (3-NT), which are known as oxidative/nitrosative stress markers, were investigated in the liver tissues of rats with metabolic syndrome model induced by a high fructose diet, and the possible protective effects of aerobic exercise in fructose-fed rats were determined. Methods: Rats were divided into four groups: control, fructose, exercise, and fructose plus exercise. Metabolic syndrome was induced in rats using 20% (w/v) fructose solution in tap water, and exercise was administered every day at the same hour for an experimental period of 8 weeks in total, 30 min a day, five days a week. After eight weeks, systolic blood pressure (SBP), serum lipid, glucose, insulin, MDA MPO, and 3-NT levels were quantified. Results: The metabolic syndrome model was successfully demonstrated by fructose administration. Compared with the C group, F caused a significant increase in SBP, serum insulin, and triglyceride levels and liver MDA, MPO, and 3-NT levels. Exercise counteracted and healed the changes in SBP, serum insulin, triglyceride, and liver MDA, MPO, and 3-NT levels in fructose-fed rats (p<0.05). Conclusion: These results indicate that high fructose consumption causes metabolic syndrome in rats, and aerobic exercise has beneficial effects on the components of metabolic syndrome. Exercise not only reduces the known risk factors of the disease, but also protects the liver while preventing oxidative and nitrosative damage caused by the MPO-H2O2 system in the liver, which increases with the effect of fructose and is necessary for the formation of non-alcoholic fatty liver disease.